Do Parents Matter? Effects of Lender Affiliation Through the Mortgage Boom and Bust - Gartenberg, Claudine (Management Science, 2014)
It is widely acknowledged that the 2007 mortgage crisis was preceded by a broad deterioration in underwriting diligence. This paper shows that this deterioration varied by the industry affiliation of mortgage lenders. Loans issued by homebuilders and stand-alone lenders were significantly less likely to default than loans issued by depository banks and affiliates of major financial institutions. I argue that homebuilders and stand-alone lenders had the least financial capacity to hold mortgages, and their resulting need to sell loans quickly on the secondary market forced them to issue safer loans. Tests of other explanations, including differences in information and incentives to avoid foreclosure externalities, receive little support. This study highlights a novel means by which firm boundaries influence firm adaptation to changing market conditions by defining the boundaries of the internal capital markets and hence the relative constraints of constituent units. This paper was accepted by Bruno Cassiman, business strategy.